Pengaruh Good Corporate Governance (GCG), Profitabilitas, dan Leverage terhadap Nilai Perusahaan (Studi pada Perusahaan Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Indah Septiani Rahayu; Triyono Adi Tristanto (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
One way investors assess the current and future success of a business is by looking at the value of the company. Therefore, increasing organizational value is the main goal of management in generating value for shareholders. Companies in the coal subsector listed on the Indonesia Stock Exchange from 2020 to 2024 are the population in this study. Eighteen companies operating in the coal subsector were randomly selected using purposive selection techniques, and financial records were used as secondary data sources. Excel and SPSS v26 are used for data processing. The value of a company is positively and significantly influenced by good corporate governance, profitability, and leverage, according to the study's conclusions. Therefore, it can be said that strong profitability, leverage, and corporate governance These three factors contribute significantly to the value of the company. A company's value is positively and significantly influenced by its profitability, the extent to which its capital structure is well managed, and the extent to which strong corporate governance standards are adhered to.